KONTRIBUSI GAYA HIDUP SEDERHANA BAGI ORANG MUDA DI ERA MODERNISASI - James Jonah Watopa; Juwinner Dedy Kasingku (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In the midst of the busy and pressure-filled modern life, many people, especially the younger generation, are facing challenges in maintaining a balanced life. Overemphasis on luxury lifestyles, following the latest trends, and material achievements often make people feel never enough, easily stressed, and lost in life’s direction. This research discusses the importance of simplicity as a key to achieving a more peaceful and meaningful life. Through a qualitative approach, this study explores views from Ellen White’s writings, emphasizing that living simply is not just about reducing excess, but also a way to draw closer to God. Simplicity helps shape a humble, thankful, and God-fearing character. Moreover, this lifestyle has a positive impact on mental health and spiritual growth. In the fast-paced, consumer-driven world, simplicity serves as a fitting and essential life principle, guiding young people towards a balanced life based on spiritual values and God’s word.